Elastography evaluation of normal thyroid gland and its comparison with diffuse non nodular enlarged thyroid gland using strain ultrasound elastography - Kumar, Sanjay; Jain, Vishal Kumar; Gupta, Ashutosh; Netam, Satya Bhuvan Singh; Gupta, Nilesh (International Journal of Research in Medical Sciences, 2019)
Background: The thyroid gland is located in the anterior part of neck, spanning between C5 and T1 vertebra and is located anterior to the thyroid and cricoids cartilage of larynx and first three tracheal rings. Ultrasonography has been widely used for diagnosis of thyroid disease it is highly regarded for its ease of use, real-time capability, portability and low cost. Methods: The current observational study was conducted in Department of Radiology, Dr. BRAM Hospital, Pt. JNM Medical College, Raipur, India. Consecutive sampling method was used for the study. All the cases coming to radiology department during the study period were taken as study subjects. Results: Of the normal subjects, author found 107 normal thyroid subjects and 53 patients were categorized into cases with diffuse non-nodular thyroid swelling groups. Of the diffuse thyroid swelling group about 85% of the study population is between 20-50 years of age group, 13.2% were <20 years of age and one patient is >50 years of age. Females to male ratio for diffuse thyroid disease is 3.4:1. Conclusions: Ultrasound elastography (USE) is a newly developed non-invasive method to evaluate and compare the elasticity of the thyroid gland and other organs like liver, prostate, parotid, breast pathologies. Its use is based on the principle that pathological changes in a tissue also changes its elasticity.